Absent Pericardium Causing Extreme Levoposition in a Child - Filippos‐Paschalis Rorris; Alexandros Tsoutsinos; Meletios Kanakis (Clinical Case Reports)
ABSTRACT During surgical repair of congenital heart defects, surgeons often come across anomalies that might not have been adequately illustrated in preoperative imaging. In this case image, we describe the absence of pericardium which was discovered during surgical repair of a sinus venosus defect in a small child.